The application of palm-oil waste as organic materials on three pineapple accessions cultivated on post-tin mining land in Bangka Island, Indonesia - Tri Lestari; RION APRIYADI; ERIES DYAH MUSTIKARINI; WAWAN SAPUTRA; YELIA MERLIN (Nusantara Bioscience, 2020)
Abstract. Lestari T, Apriyadi R, Mustikarini ED, Saputra W, Merlin Y. 2020. The application of palm-oil waste as organic materials on three pineapple accessions cultivated on post-tin mining land in Bangka Island, Indonesia. Nusantara Bioscience 12: 40-45. Tin mining activities in Bangka Island have produced a vast extent of critical lands that contain clay and tailings. Bangka local pineapple accessions have a high potential to be cultivated in the post-tin mining area as they are able to adapt to drought. The aim of this research was to investigate the growth performance of three pineapple accessions planted on post-tin mining land in Bangka by utilizing solid waste of oil palm as organic materials. The study was conducted in Dwi Makmur village, Merawang Sub-district, Bangka District from November 2017 to June 2019. The experiment used Factorial Completely Randomized Design (FCRD) with two factors: the first was three pineapple accessions (i.e. Toboali Bikang, Peranak and Bogor) and the second was palm oil solid waste (i.e. palm oil empty bunch (POEB) and palm oil bare ash (POBA)). We measured the parameters of vegetative and generative and the values were compared using Fisher test followed by Duncan Multiple Range Test (? 0.05). We also conducted organoleptic tests and total dissolved solid tests to assess the quality of the fruit. We found that the application of POEB as organic materials affected the vegetative and generative parameters. We also found that the interaction of POEB with Peranak accession resulted in the best fruit productivity. Our results suggest that Peranak accession is potential to be cultivated in post-tin mining land in Bangka with the application of palm oil empty bunch as organic materials.